Identifying Key Components of Knowledge Management Strategy in Government: A Systematic Literature Review - Putri, Sabrina Editha; Irmayani, Irni; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya (Politeknik Siber Cerdika Internasional, 2026)
Background: Amid digital transformation and the demand for adaptive public governance, Knowledge Management (KM) has become a strategic asset for government agencies. Previous studies have examined individual KM success factors—such as leadership, organizational culture, or technology readiness—yet most remain fragmented, case-specific, and lack an integrated strategic framework tailored to public sector governance. Objective: This study aims to identify key components and effective strategies for implementing KM in government organizations through a Systematic Literature Review (SLR) using the PRISMA 2020 framework. Methods: A total of 600 articles were screened from five leading scientific databases, resulting in 20 eligible studies for in-depth analysis. The review addresses two questions: (1) What are the key components of KM in government. (2) What strategies effectively support KM implementation in the public sector. Results: KM success in government rests on two interrelated domains: KM Foundation (leadership, organizational culture, structure, readiness, and technological infrastructure) and KM Solution (knowledge capture, sharing, discovery processes, regulatory mechanisms, and user-friendly systems). Nine strategic implementation areas were identified, including transformational leadership, human capital development, technology integration, performance alignment, and regulatory strengthening. Unlike prior studies that examined KM components separately, this research integrates fragmented findings into a structured and strategic framework combining foundational and operational dimensions. The study contributes theoretically by conceptualizing KM as a strategic governance capability and practically by offering policy-relevant guidance for strengthening adaptive, collaborative, and knowledge-driven public sector reform. Conclusion: An integrated and strategically aligned KM approach is essential for sustainable and effective public governance.